2015
DOI: 10.1002/ejoc.201403643
|View full text |Cite
|
Sign up to set email alerts
|

Fmox: A Base‐Labile Aldehyde Protecting Group

Abstract: A base‐labile aldehyde protecting group founded upon the 3‐Fmoc‐(1,3)‐oxazinane moiety has been developed. A series of novel or previously described acid‐labile aldehyde protecting groups were proven to be fully stable under the mild basic conditions, which completely removed the new base‐labile aldehyde protecting group. The possible reaction pathways for introducing and removing the different aldehyde protecting groups have been explored and characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…The homogeneous reaction was optimized by using the coupling product of 4‐methylbenzylamine and building block 1 [26] containing an aldehyde masked with acid‐labile 3‐Boc‐(1,3)‐oxazinane (Box) [27, 28] (Table 1). Upon exposure to trifluoroacetic acid (TFA), urea 2 was unmasked to form the corresponding aldehyde.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The homogeneous reaction was optimized by using the coupling product of 4‐methylbenzylamine and building block 1 [26] containing an aldehyde masked with acid‐labile 3‐Boc‐(1,3)‐oxazinane (Box) [27, 28] (Table 1). Upon exposure to trifluoroacetic acid (TFA), urea 2 was unmasked to form the corresponding aldehyde.…”
Section: Figurementioning
confidence: 99%
“…[15,24,25] Herein,t he novel INCIC/A 3 reactions equence was studied under classic homogeneous conditions as well as applied to solid-phasec onditions. The homogeneous reactionwas optimized by using the coupling product of 4-methylbenzylamine and building block 1 [26] containing an aldehyde masked with acid-labile 3-Boc-(1,3)-oxazinane (Box) [27,28] (Table 1). Upon exposure to trifluoroacetic acid (TFA), urea 2 wasu nmasked to form the corresponding aldehyde.…”
mentioning
confidence: 99%
“…In our continuous effort to explore the versatility of INCIC reactions, we have employed C‐nucleophiles in combination with the 3‐Boc‐(1,3)‐oxazinane (BOX) protected aldehyde building blocks 9 (Scheme ). Recent studies have revealed that the outcome of the reaction was fully dependent on both the concentration of TFA and reaction time applied.…”
Section: Figurementioning
confidence: 99%